Descripción de Pima karatauensis Tsvetkov, sp. n. de Kazajistán (Lepidoptera: Pyralidae, Phycitinae) - E. V. Tsvetkov (SHILAP, 2020)
Se describe de la provincia de Turkestán de Kazajistán a Pima karatauensis Tsvetkov, sp. n.. Male and female genitalia of this species and also habitus of imago are illustrated. The description is based on material collected by the author in Karatau Mts. in 2019.